Extracorporeal Shock Wave Lithotripsy at 60 Shock Waves/Min Reduces Renal Injury in a Porcine Model - Connors, Bret A. (2009)
PURPOSE: To determine if extracorporeal shock wave lithotripsy (ESWL) at 60 shock waves (SWs)/min reduces renal damage and hemodynamic impairment compared to treatment at 120 SWs/min. MATERIALS AND METHODS: One kidney in each of 19 juvenile pigs (7–8 weeks old) was treated at 120 or at 60 SWs/min (2000 SWs, 24kV) with an unmodified HM-3 lithotripter (Dornier Medical Systems, Kennesaw, Ga, USA). Renal function was determined before and after ESWL treatment by inulin clearance, extraction and clearance of para-aminohippuric acid. Both kidneys were then removed to measure parenchymal lesion size by sectioning the entire kidney and quantifying the size of the hemorrhagic lesion in each slice. RESULTS: ESWL at 60 SWs/min significantly reduced the size of the acute morphological lesion compared to 120 SWs/min (0.42% vs 3.93% of functional renal volume, (P = 0.011) and blunted the decrease in glomerular filtration rate and renal plasma flow normally seen after treatment at 120 SWs/min. CONCLUSIONS: Treatment at a firing rate of 60 SWs/min produces less morphological injury and causes less alteration in renal hemodynamics than treatment at 120 SWs/min in the pig model of ESWL-induced renal injury.